Implementasi Algoritma Huffman untuk Kompresi Gambar pada Jaringan 6LoWPAN - Kuni Yustika Dewi; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Current technology requires a network that able to collect data continuously. With sensors that can collect data and able to communicate on a wireless network, communication will be possible. One of the wireless networks that can monitor certain environmental conditions in different areas is the Wireless Sensor Network (WSN). However, due to the small transmission capacity of WSN, the monitoring process requires a method that can reduce the size of the data sent and requires a communication module that allows low-power devices to communicate with each other. One method to perform image compression is the Huffman Algorithm. And the communication module which excels in data transmission capacity and has low power consumption is 6Lowpan. The results obtained from the data size performance test, namely the compression method can reduce the image size by 25% from the previous image size and can reduce the number of packet sizes by 78% of the number of packets before being compressed. In addition, it can be concluded that the compression method can increase the packet delivery time, but the compression method can reduce the success rate of packet delivery and the average delay time in packet transmission.